A scuola con gli antichi - Becchi, Egle (Studi sulla Formazione/Open Journal of Education, 2019)
In the lively debate about a return to the classics, scholars emphasize the new meaning of this return. They dont accept a panegyrical approach, but insist on a return which give rise to questions important at the present time. I consider four scholars, Mario Vegetti, Salvatore Settis , Luciano Canfora, Maurizio Bettini, and analyze their criticism , particularly to the liceo classico, as it is organized in the Riforma Gelmini. I briefly discuss the educational methods , and what has been done to improve the study of greek and latin language and culture. At last I present some of the proposals made by Settis, Canfora and Bettini in order to update a return to the classics in the school.